STEM-BASED PHYSICS LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS OF BUDI DARMA UNIVERSITY STUDENTS - Melda Panjaitan (Edumaniora : Jurnal Pendidikan dan Humaniora, 2025)
This study aims to analyze the effectiveness of STEM (Science, Technology, Engineering, and Mathematics)-based physics learning models in improving students' critical thinking skills. Using quantitative and qualitative approaches, this study involved two groups of physics education students in the second semester at Budi Darma University, namely an experimental class using a STEM-based model and a control class using conventional methods. The research instruments include pretest and posttest, observation, and interview. The results showed a significant improvement in critical thinking skills in the experimental group compared to the control group. These findings show that the STEM approach can be used as an effective strategy in developing high-level thinking skills in students